Half a mile or a world apart? A systemic duoethnographic inquiry into our experience of social class in the UK - Evans, Rachel Julia; Hall, Steven (Murmurations: Journal of Transformative Systemic Practice, 2022)
These reflective auto-biographical /ethnographic pieces are based on experiences of social class during our childhoods. We go on to reflect upon these from our current perspectives within the UK public sector. Born in 1975, we grew up living half a mile apart from each other in Kings Norton, Birmingham. We met as teenagers and were reacquainted in our 40s. Our childhoods were worlds apart from the perspective of social class and social deprivation. We see these same class divides in our everyday encounters in our work contexts. This paper emerged from conversations regarding our contrasting experiences and explores how reflecting on social class may impact upon practice. The article uses a duoethnographic and systemic inquiry methodology and we use a method we have devised for the purpose called a “ripple effect” to reflect on each other’s writings. There is so much we would have liked to expand further upon in this paper. Through the writing we have recognised many further directions that the discussion could have moved in, leaving room for further debate.